An attempt for increasing the efficiency of penning source of Н ⁻ ions with a metal hydride cathode - Sereda, I.; Ryabchikov, D.; Hrechko, Ya.; Babenko, Ie. (Вопросы атомной науки и техники, 2020)
The possibility of increasing the current of negative hydrogen ions extracted in the longitudinal direction from a Penning discharge with a metal hydride cathode by reducing the anode-cathode distance is shown. The features of Н ⁻ ions emission have been revealed depending on the electric shift on the metal hydride cathode and the external magnetic field. The power parameters of the electromagnetic filter have been optimized for the separation of negative ions from the extracted flux of charged particles. The current of H ⁻ ion beam was obtained at the level of 16 μA with hydrogen supply only from the metal hydride cathode and at the level of 0.1 mA at external supply from the balloon.